Regulating dispute resolution: ADR and access to justice at the crossroads - Steffek, Felix; Genn, Hazel G.; Greger, Reinhard; Menkel-Meadow, Carrie; Unberath, Hannes (Hart, 2013)
This book proposes a principled approach to the regulation of dispute resolution. It covers dispute resolution mechanisms in all their varieties, including negotiation, mediation, conciliation, expert opinion, mini-trial, ombudsman procedure, arbitration and court adjudication. The authors present a transnational Guide for Regulating Dispute Resolution (GRDR). The regulatory principles contained in this Guide are based on a functional taxonomy of dispute resolution mechanisms, an open normative framework and a modular structures of regulatory topics. The Guide for Regulating Dispute Resolution is formulated and commented upon in a concise manner to assist legislators, policy-makers, professional associations, practitioners and academics in thinking about which solutions best suit local and regional circumstances
Keywords: Aufsatzsammlung; Internationale Schiedsgerichtsbarkeit; Mediation; Zivilprozess